IJCM_31A: Menstrual characteristics and school absenteeism among adolescent school girls of Aligarh--A Cross-sectional Study - Karthika P; Abedi Ali Jafar; Mehnaz Saira; Tabassum (Wolters Kluwer Medknow Publications, 2024)
Background: Menstruation is a significant event during adolescence. It is often a challenging period for adolescent girls since it poses significant challenges. The stigma associated with menstruation, difficulties due to menstrual disorders, and period poverty can often lead to school absenteeism and school dropout among girls. Objectives: 1) To identify menstrual characteristics and explore the symptoms associated with menstrual cycles among adolescent schoolgirls of Aligarh. 2) To examine whether adolescent schoolgirls experience absenteeism during menstruation and to elucidate the reasons for such occurrences. Methodology: This is a cross-sectional study carried out among adolescent school girls of Aligarh. Two urban and two rural schools were selected randomly from the co-educational schools in Aligarh, with inclusion criteria comprising adolescent girls in grades six to ten who had experienced menarche at least six months prior. Parental consent and participant assent were obtained, resulting in the participation of 164 students. Data collection was conducted through a questionnaire method. Results: The respondents' average age was 14.5±1.33 years, with 84.1% exhibiting regular menstrual cycles out of the 164 participants. The mean age at menarche was 12.7±1.02, and the average duration of menstruation was 4.90±1.54 days. Only 12% of students did not experience pain during menstruation, while the majority reported mild (35.4%), pain only on the first day (30.5%), or excessive (2.8%) pain. Predominant pre-menstrual symptoms included irritability, mood disturbances, and breast tenderness. Despite these challenges, a majority of students (84.1%) affirmed not taking leave during menstruation. Among those who did, the reasons included a lack of facilities for changing pads, insufficient disposal systems for pads, and dysmenorrhoea. Conclusion: This study sheds light on the menstrual characteristics and challenges faced by adolescent schoolgirls in Aligarh. Despite the challenges, the students attend school during menstruation which shows the importance of targeted interventions to address the challenges